A Comparison of intra-oral digital imaging modalities: Charged Couple Device versus Storage Phosphor Plate - Anas, A; Asaad, JM; Tarboush, K A (International Journal of Health Sciences, 2010)
Abstract Background This in vitro study was conducted to compare the accuracy of two digital image receptors in identifying the location of tip of a fine endodontic file and radiographic apex in mandibular posterior teeth. Methods Fourteen human cadaver mandibles with retained molars were selected. These molars were prepared for access to the canals and an endodontic file #10 was introduced into the canal at one of the three random distances from the apex of the tooth. At each distance from the apex and at the apex of the tooth, images were made with two different image receptors; DenOptix storage phosphor plates and Gendex CCD sensor. Six raters viewed all the images for identification of the radiographic apex of the tooth and the tip of the endodontic file. Images were displayed randomly under standardized conditions. To assess intra-rater reliability, all the examiners viewed a subset of randomly selected images again after a time period of one week, inter rater reliability was also assessed. At the end of the study, teeth were extracted and the length of the canals measured to obtain a gold standard. Results T-test revealed a significant main effect for the type of image, indicating that raters’ error in identifying structures of interest was significantly higher for Denoptix storage phosphor plates. Conclusion The results of the study clearly reveal that Gnedex CCD produce most reliable images for Root Canal working length estimation when compared with Denoptix SPP.